Effect of image and brand trust on loyalty of cement baturaja consumers - Santri, Basthony; Wahab, Zakaria; Widiyanti, Marlina; Shihab, Muchsin Saggaff (International research journal of management, IT and social sciences, 2021)
This research was conducted to determine brand image and brand trust on consumer loyalty to Baturaja cement. All Baturaja cement consumers from September 2020 to October 2020 in the Lampung region were involved in this study. Likewise, a sample of 150 people obtained through a purposive sampling technique with several criteria of determination. Using a questionnaire distributed to all consumers, we can process the data using multiple linear regression analysis. Multiple linear analysis shows that brand image positively and significantly affects customer loyalty to the Baturaja cement brand. Likewise, brand trust has a positive and significant effect on consumer loyalty to the Baturaja cement brand. Meanwhile, the brand image is expected to update by making the product tagline more attractive, both from the color type, the tagline size that can be easier to remember and attract consumers. Brand trust is expected that the company can improve product quality and carry out more attractive promotions, with the status of a limited company Semen Baturaja does not guarantee that consumers will prefer Baturaja cement products.